51: Inhaled and Systemic Corticosteroid Administration to Preterm Infants Across Canadian NICUs. Issue 6 (1st June 2014) - Derynck, MR; Shah, PS; Seshia, M; Bouali, N Rouvinez; Yoon, EW; Lee, SK; Dow, K
Abstract: BACKGROUND: Inhaled corticosteroids (ICS) are used to treat BPD despite limited evidence of efficacy and safety. Systemic corticosteroids (SCS) yield significant morbidity, but have not been recently examined in a large population-based study. OBJECTIVES: To examine variation in ICS and SCS use and neonatal outcomes across Canadian NICUs. DESIGN/METHODS: A retrospective cohort study of neonates 22≤ GA <29 weeks, receiving steroids for BPD, and admitted between 2010 and 2012 was conducted using data from the Canadian Neonatal Network (CNN) database. Demographics, ventilation status, and rates of mortality, BPD, nosocomial infection (NI), ROP, and NEC were compared between those who received ICS, SCS, and both ICS+SCS, and those who did not. ICS and SCS use were compared across sites. RESULTS: A total of 4087 infants met inclusion criteria; 368 (9%) received SCS, 234 (6%) ICS, and 137 (3%) both. Baseline comparison revealed a significantly lower GA (P<0.0001), birth weight (P<0.0001) and higher SNAP II score (P<0.0001) among those who received ICS and/or SCS. Antenatal steroid use was not associated with ICS and/or SCS use (P=0.05). Mortality was more common among those who received SCS after exclusion of neonates that died prior to median SCS initiation (AOR 4.98 [95% CI 3.15 to 7.88]). Severe ROP was more common in infants who received SCS (AOR 2.95 [95% CI 2.16 to 4.05]). NEC and NI preceded steroid use. Site-specific BPD rates did not correlate with SCS or ICS use. SCS use varied significantly between units (AOR range 0.0 [95% CI 0.0 to 0.0) to 4.2 (95% CI 1.1 to 16]). ICS use ranged from 0% to 39.8% (median 1.2% [IQR 0% to 8.3%]); nine sites did not use ICS. CONCLUSIONS: ICS and SCS are commonly used medications in Canadian NICUs, although considerable site variation exists. Further study of efficacy and safety is required to develop guidelines for neonatal steroid use.